Dakwah dan Bimbingan Islami - A Gazali (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2022)
This paper reviewed how the materials and methods of spiritual guidance with an Islamic approach shape the spirituality of Islam. This study also described the relationship of Islamic spiritual guidance which is correlated with the Islamic da'wah movement. The literature study is a method of research that used as a method in this paper, this method explored the data contained in the literatures that discusses this theme. Humans are creatures that have two environments, physical and spiritual. Both can engage in the relationship between guidance and individual or social problems. Therefore, the need for guidance, both in terms of physical and spiritual aspects is a necessity. Islam is a religion of revelation, and its teachings aim to spread mercy for both humans and other creatures. Islam has materials and methods to guide humans to reach this grace. The material is in the Islamic da'wah movement, and the method is in Islamic spiritual guidance.